Procedures for Issuing the Confirmed Ruling for Customary Divorce in Algerian Legislation - Layachi, Afaf Lamia (Journal of Legal Studies and Researches, 2021)
The Algerian legislator has declared in Article 49 of the Family Code that divorce is valid only by judicial decision, which is an established principle, but the judiciary has departed from this principle by establishing customary divorce, retroactively through legal action. The Algerian legislator has referred to the case of customary divorce with special procedures for judgment, which is different in the case of customary divorce, since it is different from ordinary divorce because it is the result of the judiciary.Once these procedures have been followed, the usual divorce decision is made and confirmed to make this provision valid.